Investigating the reasons for missing an outpatient appointment in Royal Hospital, Sultanate of Oman: Perspectives of patients and medical staff in a survey. Issue 1 (11th January 2022) - Alawadhi, Ahmed; Palin, Victoria; van Staa, Tjeerd
Abstract: Introduction: Missed appointments are a major health issue in the healthcare systems globally. They directly impact on the use of hospital resources, patient's health, and can lead to patient's dissatisfaction. This study was conducted to assess the reasons for missing a hospital appointment. Methods: A survey was conducted with a randomly selected sample of patients who missed their outpatient appointment in Royal hospital, Sultanate of Oman, from March to April 2021 in six clinics. Patients were interviewed via telephone to answer a structured survey. In addition, a self‐administered survey was distributed to medical staff to explore their perspectives. Results: Two hundred eighty patients and 52 medical staff participated in the study. Frequent patient‐reported reasons for missed appointment were transportation difficulties (11.4%), no longer needing (7.5%), or forgetting the appointment (6.8%); staff‐reported reasons were transportation (23.8%), no SMS received (16.9%), and forgetting the appointment (15.4%). Frequencies of reasons varied substantially between clinics. Family obligations were the main theme in obstetrics (odds ratio [OR] 9.48; 95% confidence interval [CI] 2.66‐33.78) and in diabetes clinic (OR 10.55; 95% CI 2.68‐38.58), where transportation issue was the main theme in Oncology clinic (OR 4.83; 95% CI 1.11‐21.02). The recommendations for improvement were mainly around improving the reminder system, the use of telephone reminders, and developing a flexible appointment scheduling system. Conclusion: Knowing the reasons for missed appointment from patients and health professionals can help to develop effective interventions. The heterogeneity between clinics in reasons for missed appointment indicates for interventions tailored to clinic and frequent reasons.